Website Based Cibendung Village Information System Design - Triyadi, Evan; Sigit Sugiyanto (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2024)
The design of the Cibendung Village information system aims to manage, access and record Cibendung Village so that information about Cibendung Village so that the information presented is important, up-to-date, interesting information and has become a lot of public attention to be more open. Therefore, the Cibendung Village Website has information features about media and communication about Cibendung Village. This feature is to get a lot of information to people who are more open than other social media such as Facebook, Twitter, Instagram and others and easy access to the website. Therefore, a web-based Cibendung Village Website was created using the waterfall method. This waterfall model provides sequential software starting from data analysis, design, coding, and testing implementation. After going through these stages, A Website-based Cibendung Village website was created to retrieve data, manage the website and access the website online to facilitate website access and get related information about Cibendung Village.